Development of Problem-Based Learning Student Worksheets to Facilitate Students’ Problem Solving Skills - Sri Wahyuni; Yuni Sri Rahayu; Sifak Indana (Jurnal Penelitian Pendidikan IPA, 2020)
The purpose of this study was to develop Problem-Based Learning student worksheets on bioremediation material to facilitate students authentic problem solving skills. The development used a procedural development model called ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were Biology Students at Surabaya State University. Data collection used validation, observation, and test techniques. Student worksheets quality measurement obtained by a rating scale instrument in the form of a validation sheet. The developed teaching materials were in the form of Semester Learning Design, Unit Of Lectures, Student worksheets, and problem solving skills-based question for evaluation purposed. This developed teaching materials had been validated by experts, with scores of SLD 3.36, UOL scores 3.44, Student worksheets were 3.36 respectively. In addition, the average score of practicality and effectiveness in pre-test and post-test of the developed teaching materials were 4.00, 1.85, and 3.40 respectively. All the developed teaching materials were in very good qualifications. Based on data analyzed, it could be concluded that the developed student worksheets on bioremediation material was valid so that it can facilitate authentic problem solving skills in Biology Students at State University of Surabaya and is feasible to be used as a teaching learning materials